Ekonomi SharÃ®âah dan Ketidakadilan Kapitalisme Global - Harisudin, MN (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
This paper understands that the SharÃ®âah Economics is a serious contender for the modern global capitalistic economic system. Capitalism has been responsible for the collapse of not only the global economic system but also the moral deterioration of human being. Injustice is the main mark of capitalism. Hence, in a capitalistic society, no law of the game is upheld economically speaking. The strong and the rich rule. The weak is always a victim. This is the main concern of this paper, vis-Ã -vis which it introduces the SharÃ®âah perspective as providing a good alternative. The paper first speaks of the sources of this âIslamicâ system -namely the Qurâan, the Sunna, Ijma and Qiyas- and then delves into its heart, namely justice. The study holds that the main imprint ot Syariâ ah economic system is justice. Being divinely revealed, this system is always in line with the very nature of man as a social being whose responsibility it is to do something beneficial for his fellow human being. Man is not created solely to accumulate wealth, but to serve God, his religion, his community by using wealth among others. Hence, wealth is not the goal, but the means. The goal that every man wants to acquire is happiness. SharÃ®âah Economicsâthe paper argues- is ordained to provide a practical guideline toward happiness.